Temperature dependence of clumped isotopes (∆47) in aragonite (IEDA: EarthChem Library)
This dataset contains (meta)data for all clumped isotope measurements carried out for the manuscript titled \"Temperature dependence of clumped isotopes (∆47) in aragonite\". These are clumped isotope measurements of aragonitic shells from lab-grown temperature-controlled Arctica islandica bivalves used to test the clumped isotope method and its calibration on aragonites.